Academy of Management Annual Meeting 1997 (Academy of Management Journal, 1997)
Why are some entrepreneurs more able to learn from failures, while others are not?To address this controversial but crucial research question, combining experiential learning theory and an error management perspective, this study builds a conceptual model to explore the relationship between failure experience and learning from failure, as well as the moderating role of error orientation.Using a survey sample of 237 high-technology ventures in China, the results show that: (1) The volume of failure experience affects learning from failure negatively; (2) The volatility of failure experience affects learning from failure positively; (3) Error competence plays a positive moderating role in the relationship between the volume of failure experience and learning from failure; and, (4) Error strain plays a negative moderating role in the relationship between the volatility of failure experience and learning from failure.The results reveal that the level of entrepreneurs' learning behaviours with different failure experience not only depends on the nature of failure experience but also their individual error orientation, which functions like a catalyst that promotes failure experience into learning behaviour or not.